Detection of functional structures in isolated perfused pig heart: methods and technical principles - Hiller, Michael; Rauh, Robert; Trinks, Tobias; Kessler, Manfred (Proceedings Volume 4623, Functional Monitoring and Drug-Tissue Interaction, 2002)
Light scattering in living heart tissue is mainly caused by mitochondria, but also by actin and myosin filaments, glycogen particles and others. In living tissue these subcellular structures are not stable but rather in a permanent change. Thus, one should be able to perceive the status of scattering structures by measurement of backscattered light in microvolumes. Our recent efforts aimed at detecting these structures by use of micro lightguides and scanning tissue spectroscopy technique (EMPHO II SSK) at isolated perfused pig hearts. The paper describes the technical principles of the scanning technique and gives an overview of our latest result